Analysis Of Changes In Nitric Oxide (NO) And F2-Isoprostane Levels After The 30 Km Cycling Event In The Makassar Bike Community - Risna Yunita; Ilhamjaya Pattelongi; Andi Ariyandy; Andi Wardihan Sinrang; Djohan Aras; Nukhrawi Nawir (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to determine changes in Nitric Oxide (NO) and F2-Isoprostane levels after a 30 km cycling event in the Makassar cycling community. This research was a pre-experimental study with a one-group pretest & post-test design with 30 cyclists as subjects in the city of Makassar, men aged 30-60 years. Blood sampling was carried out pre-event and post-event cycling as far as 30 Km. Measurement of F2-Isoprostane & Nitric Oxide levels using the ELISA method. Data analysis used the Wilcoxon test to see changes in Nitric Oxide (NO) and F2-Isoprostane levels after participating in a 30 Km cycling event. Data analysis using the Mann-Whitney test was used to see differences in changes in Nitric Oxide (NO) and F2-Isoprostane levels in the age group, average speed, exercise category, BMI, and smokers. Spearman test to see the correlation of changes in Nitric Oxide (NO) and F2-Isoprostane levels. The results of this study found that the 30 km cycling event had a significant effect on changes in Nitric Oxide (NO) levels which could improve the function of the vascular endothelium with p=0.0001. Meanwhile, the 30 km cycling event had no significant effect on changes in F2-Isoprostane levels, which meant that it had no risk of oxidative stress and tissue damage (p=0.688). There is no positive correlation between changes in Nitric Oxide (NO) levels and changes in F2-Isoprostane levels, which means that changes in the repair of vascular endothelial function seem to suppress free radical production which leads to oxidative stress after cycling as far as 30 Km.